Research and Consulting in Data-Driven Strategic Product Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Dumitrescu, Roman (Journal of Systemics, Cybernetics and Informatics)

Social interactions and asset pricing bubbles - Steiger, Sören; Pelster, Matthias (Journal of Economic Behavior & Organization)

A Discrete and Continuous Study of the Max-Chain-Formation Problem – Slow Down to Speed Up - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Stabilization, Safety, and Security of Distributed Systems - 22nd International Symposium, SSS 2020, Austin, Texas, USA, November 18-21, 2020, Proceedings)
Most existing robot formation problems seek a target formation of a certain minimal and, thus, efficient structure. Examples include the Gathering and the Chain-Formation problem. In this work, we study formation problems that try to reach a maximal structure, supporting for example an efficient coverage in exploration scenarios. A recent example is the NASA Shapeshifter project, which describes how the robots form a relay chain along which gathered data from extraterrestrial cave explorations may be sent to a home base. As a first step towards understanding such maximization tasks, we introduce and study the Max-Chain-Formation problem, where $n$ robots are ordered along a winding, potentially self-intersecting chain and must form a connected, straight line of maximal length connecting its two endpoints. We propose and analyze strategies in a discrete and in a continuous time model. In the discrete case, we give a complete analysis if all robots are initially collinear, showing that the worst-case time to reach an $\varepsilon$-approximation is upper bounded by $\mathcal{O}(n^2 \cdot \log (n/\varepsilon))$ and lower bounded by $\Omega(n^2 \cdot~\log (1/\varepsilon))$. If one endpoint of the chain remains stationary, this result can be extended to the non-collinear case. If both endpoints move, we identify a family of instances whose runtime is unbounded. For the continuous model, we give a strategy with an optimal runtime bound of $\Theta(n)$. Avoiding an unbounded runtime similar to the discrete case relies crucially on a counter-intuitive aspect of the strategy: slowing down the endpoints while all other robots move at full speed. Surprisingly, we can show that a similar trick does not work in the discrete model.

Preservation of Bifurcations of Hamiltonian Boundary Value Problems Under Discretisation - McLachlan, Robert I; Offen, Christian (Foundations of Computational Mathematics)
We show that symplectic integrators preserve bifurcations of Hamiltonian boundary value problems and that nonsymplectic integrators do not. We provide a universal description of the breaking of umbilic bifurcations by nonysmplectic integrators. We discover extra structure induced from certain types of boundary value problems, including classical Dirichlet problems, that is useful to locate bifurcations. Geodesics connecting two points are an example of a Hamiltonian boundary value problem, and we introduce the jet-RATTLE method, a symplectic integrator that easily computes geodesics and their bifurcations. Finally, we study the periodic pitchfork bifurcation, a codimension-1 bifurcation arising in integrable Hamiltonian systems. It is not preserved by either symplectic on nonsymplectic integrators, but in some circumstances symplecticity greatly reduces the error.

Detection of high codimensional bifurcations in variational PDEs - Kreusser, Lisa Maria; McLachlan, Robert I; Offen, Christian (Nonlinearity)

Analysis of Hamiltonian boundary value problems and symplectic integration - Offen, Christian
Ordinary differential equations (ODEs) and partial differential equations (PDEs) arise in most scientific disciplines that make use of mathematical techniques. As exact solutions are in general not computable, numerical methods are used to obtain approximate solutions. In order to draw valid conclusions from numerical computations, it is crucial to understand which qualitative aspects numerical solutions have in common with the exact solution. Symplecticity is a subtle notion that is related to a rich family of geometric properties of Hamiltonian systems. While the effects of preserving symplecticity under discretisation on long-term behaviour of motions is classically well known, in this thesis (a) the role of symplecticity for the bifurcation behaviour of solutions to Hamiltonian boundary value problems is explained. In parameter dependent systems at a bifurcation point the solution set to a boundary value problem changes qualitatively. Bifurcation problems are systematically translated into the framework of classical catastrophe theory. It is proved that existing classification results in catastrophe theory apply to persistent bifurcations of Hamiltonian boundary value problems. Further results for symmetric settings are derived. (b) It is proved that to preserve generic bifurcations under discretisation it is necessary and sufficient to preserve the symplectic structure of the problem. (c) The catastrophe theory framework for Hamiltonian ODEs is extended to PDEs with variational structure. Recognition equations for A-series singularities for functionals on Banach spaces are derived and used in a numerical example to locate high-codimensional bifurcations. (d) The potential of symplectic integration for infinite-dimensional Lie-Poisson systems (Burgers’ equation, KdV, fluid equations, . . . ) using Clebsch variables is analysed. It is shown that the advantages of symplectic integration can outweigh the disadvantages of integrating over a larger phase space introduced by a Clebsch representation. (e) Finally, the preservation of variational structure of symmetric solutions in multisymplectic PDEs by multisymplectic integrators on the example of (phase-rotating) travelling waves in the nonlinear wave equation is discussed.

A Novel Higher-order Weisfeiler-Lehman Graph Convolution - Damke, Clemens; Melnikov, Vitaly; Hüllermeier, Eyke (Proceedings of the 12th Asian Conference on Machine Learning (ACML 2020))
Current GNN architectures use a vertex neighborhood aggregation scheme, which limits their discriminative power to that of the 1-dimensional Weisfeiler-Lehman (WL) graph isomorphism test. Here, we propose a novel graph convolution operator that is based on the 2-dimensional WL test. We formally show that the resulting 2-WL-GNN architecture is more discriminative than existing GNN approaches. This theoretical result is complemented by experimental studies using synthetic and real data. On multiple common graph classification benchmarks, we demonstrate that the proposed model is competitive with state-of-the-art graph kernels and GNNs.
Keywords: graph neural networks; Weisfeiler-Lehman test; cycle detection

Process design for the forming of semi-tubular self-piercing rivets made of high nitrogen steel
The aim to reduce pollutant emission has led to a trend towards lightweight construction in car body development during the last years. As a consequence of the resulting need for multi-material design, mechanical joining technologies become increasingly important. Mechanical joining allows for the combination of dissimilar materials, while thermic joining techniques reach their limits. Self-piercing riveting enables the joining of dissimilar materials by using semi-tubular rivets as mechanical fasteners. The rivet production, however, is costly and time-consuming, as the rivets generally have to be hardened, tempered and coated after forming, in order to achieve an adequate strength and corrosion resistance. A promising approach to improve the efficiency of the rivet manufacturing is the use of high-strength high nitrogen steel as rivet material because these additional process steps would not be necessary anymore. As a result of the comparatively high nitrogen content, such steels have various beneficial properties like higher strength, good ductility and improved corrosion resistance. By cold bulk forming of high nitrogen steels high-strength parts can be manufactured due to the strengthening which is caused by the high strain hardening. However, high tool loads thereby have to be expected and are a major challenge during the production process. Consequently, there is a need for appropriate forming strategies. This paper presents key aspects concerning the process design for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel. The aim is to produce the rivets in several forming stages without intermediate heat treatment between the single stages. Due to the high strain hardening of the material, a two stage forming concept will be investigated. Cup-backward extrusion is chosen as the first process step in order to form the rivet shank without forming the rivet foot. Thus, the strain hardening effects in the area of the rivet foot are minimized and the tool loads during the following process step can be reduced. During the second and final forming stage the detailed geometry of the rivet foot and the rivet head is formed. In this context, the effect of different variations, for example concerning the final geometry of the rivet foot, on the tool load is investigated using multistage numerical analysis. Furthermore, the influence of the process temperature on occurring stresses is analysed. Based on the results of the investigations, an adequate forming strategy and a tool concept for the manufacturing of semi-tubular self-piercing rivets made of high-strength steel are presented.
Keywords: high nitrogen steel; self-piercing riveting; joining by forming; bulk forming; tool design

Optimierung von JMCTest beim Testen von Inter Method Contracts - Mayer, Stefan

Mining Crowdsourcing Problems from Discussion Forums of Workers - Nouri, Zahra; Wachsmuth, Henning; Engels, Gregor (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)

Persuasiveness of News Editorials depending on Ideology and Personality - El Baff, Roxanne; Al-Khatib, Khalid; Stein, Benno; Wachsmuth, Henning (Third Workshop on Computational Modeling of People's Opinions, Personality, and Emotions in Social Media (PEOPLES 2020))

Mobile Medien – Medienpädagogische und technische Grundlagen, Potential für den Deutschunterricht und Beispiele. - Herzig, Bardo; Martin, Alexander; Klar, Tilman-Mathies (Deutsch Digital. Band 1 Theorie (2. Aufl.))

Als Wirtschaftsinformatiker die digitale Transformation in Organisationen gestalten - Kundisch, Dennis; Beverungen, Daniel

Argument from Old Man's View: Assessing Social Bias in Argumentation - Spliethöver, Maximilian; Wachsmuth, Henning (Proceedings of the 7th Workshop on Argument Mining (ArgMining 2020))

Semi-Supervised Cleansing of Web Argument Corpora - Dorsch, Jonas; Wachsmuth, Henning (Proceedings of the 7th Workshop on Argument Mining (ArgMining 2020))

Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren - Otroshi, Mortaza; Meschut, Gerson
Der Karosseriebau ist zunehmend durch die Verwendung unterschiedlicher Werkstoffe in Mischbauweise gekennzeichnet, was zu einem Einsatz von mechanischen Fügeverfahren geführt hat. Hieraus resultieren die Zielsetzungen, die mechanischen Fügeverfahren in ihrer Effizienz und ihren Einsatzbereichen zu erweitern, sowie die Anzahl der Experimente zu reduzieren und Entwicklungszyklen zu verkürzen. Dies erfolgt mit Unterstützung der numerischen Simulation. Neben der Beschreibung des plastischen Verhaltens gilt es auch, das Schädigungsverhalten abzubilden. Der Fügeprozess bzw. die Fügerichtung erfolgt senkrecht zur Blechoberfläche und führt somit zu einem dreidimensionalen Zustand der Fügelemente. Hieraus leitet sich die Herausforderung ab, das Werkstoffversagen in Abhängigkeit der Beanspruchungssituation zu beschreiben. Ein einfacher Ansatz zur Abbildung des Durchdringens ist ein geometrisches Trennkriterium. Ein solches Kriterium basiert i.d.R. auf einem experimentell beobachteten Verhalten und ist somit nicht prognosefähig für Variationen bzgl. Werkzeugkonfigurationen, Blechdicken- und Werkstoffgüten-Kombinationen. In diesem Projekt wird das Schädigungsmodell GISSMO (Generalized Incremental Stress State dependent damage Model) verwendet, um die Entwicklung der duktilen Schädigung zu beschreiben und den Bruchbeginn während des Stanzniet- und Schneidclinchens vorherzusagen. Der Spannungszustand während der Prozesssimulation wird untersucht und die verschiedenen Schädigungsproben werden experimentell erprobt, um die Versagenskurven zu charakterisieren. Die Versagenskurven werden im Schädigungsmodell GISSMO definiert. Um die Genauigkeit des Modells zu gewährleisten, wird die Verifizierung des Modells durch die Simulation von Schädigungsproben mit dem Schädigungsmodell durchgeführt. Zur Validierung des Modells wird die Simulation des Fügeprozesses mit dem Schädigungsmodell durchgeführt und die Ergebnisse von Simulation und Experiment verglichen. Darüber hinaus werden Sensitivitätsanalysen durchgeführt, um die Einflüsse der Fertigungsprozesse, der Lackierung und des Diskretisierungsgrades auf das Schädigungsverhalten des Materials zu identifizieren. Das IGF-Vorhaben „Methodenentwicklung zur Schädigungsmodellierung für die numerische Prozesssimulation mechanischer Fügeverfahren" der Forschungsvereinigung EFB e.V. wurde unter der Fördernummer AiF 19452N über die Arbeitsgemeinschaft industrieller Forschungsvereinigungen (AiF) im Rahmen des Programms zur Förderung der Industriellen Gemeinschaftsforschung (IGF) vom Bundesministerium für Wirtschaft und Energie aufgrund eines Beschlusses des Deutschen Bundestages gefördert. Der Abschlussbericht ist als EFB-Forschungsbericht Nr. 527 erschienen und bei der EFB-Geschäftsstelle und im Buchhandel erhältlich.

Linear damage accumulation of self-pierce riveted joints - Masendorf, Lukas; Wächter, Michael; Horstmann, Stephan; Otroshi, Mortaza; Esderts, Alfons; Meschut, Gerson
Joining technology is regarded as a key technology for reducing energy consumption and CO2 imitation as well as the use of innovative materials and development of new, resource-saving products. Punch riveting is a widely used and established joining process in many sectors. The white and brown goods, electrical engineering, construction and, in particular, the automotive industry are some of the sectors mentioned here. Since the design and assessment of punch rivet components with regard to structural durability can only be carried out experimentally using prototypes due to a lack of experience and calculation concepts, the improvement of this uneconomical and time-consuming procedure is the goal of this contribution. Therefore, a numerical simulation and design method for cyclically loads punched riveted joints shall be introduced. This concept shall be based on the notch strain concept. The following steps are necessary to achieve the goal shown above: Tensile tests on all materials involved in the joint for determination of tensile strength and quasi-static stress-strain curves Estimation of the cyclic material properties from the tensile strength in order to obtain the strain-life curve and the cyclic stress-strain curve Estimation of mean stress sensitivity from the tensile strength to conduct an amplitude transformation for variable amplitude loadings. Execution of a 2D forming simulation of the joining process to determine the geometry and the stresses and degrees of deformation present in the connection Transferring the results of the forming simulation into a static-mechanical load simulation for determining the relation between the external load and the elastic-plastic strain at the critical point Estimation of the service life by means of the damage parameter Wöhler curves calculated from the strain-life curve In order to verify the simulation and calculation method, service life investigations have been carried out on punched riveted components under constant and variable amplitude load. The test results, as well as the workflow through the fatigue assessment and its accuracy in estimation the fatigue life will be shown in this contribution.
Keywords: punch rivet; notch strain conept; structural durability

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (28th Annual European Symposium on Algorithms (ESA 2020))
Let G = (V,E) be an undirected graph on n vertices with non-negative capacities on its edges. The mincut sensitivity problem for the insertion of an edge is defined as follows. Build a compact data structure for G and a given set S ⊆ V of vertices that, on receiving any edge (x,y) ∈ S×S of positive capacity as query input, can efficiently report the set of all pairs from S× S whose mincut value increases upon insertion of the edge (x,y) to G. The only result that exists for this problem is for a single pair of vertices (Picard and Queyranne, Mathematical Programming Study, 13 (1980), 8-16). We present the following results for the single source and the all-pairs versions of this problem. 1) Single source: Given any designated source vertex s, there exists a data structure of size 𝒪(|S|) that can output all those vertices from S whose mincut value to s increases upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(|S|). 2) All-pairs: There exists an 𝒪(|S|²) size data structure that can output all those pairs of vertices from S× S whose mincut value gets increased upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(k), where k is the number of pairs of vertices whose mincut increases. For both these versions, we also address the problem of reporting the values of the mincuts upon insertion of any given edge. To derive our results, we use interesting insights into the nearest and the farthest mincuts for a pair of vertices. In addition, a crucial result, that we establish and use in our data structures, is that there exists a directed acyclic graph of 𝒪(n) size that compactly stores the farthest mincuts from all vertices of V to a designated vertex s in the graph. We believe that this result is of independent interest, especially, because it also complements a previously existing result by Hariharan et al. (STOC 2007) that the nearest mincuts from all vertices of V to s is a laminar family, and hence, can be stored compactly in a tree of 𝒪(n) size.
Keywords: Mincut; Sensitivity; Data Structure

Reinforcement Learning for Virtual Network Embedding in Wireless Sensor Networks - Afifi, Haitham; Karl, Holger (2020 Thirteenth International Workshop on Selected Topics in Mobile and Wireless Computing (STWiMob'2020))
Upcoming sensing applications (acoustic or video) will have high processing requirements not satisfiable by a single node or need input from multiple sources (e.g., speaker localization). Offloading these applications to cloud or mobile edge is an option, but when running in a wireless senor network (WSN), it might entail needlessly high data rate and latency. An alternative is to spread processing inside the WSN, which is particularly attractive if the application comprises individual components. This scenario is typical for applications like acoustic signal processing. Mapping components to nodes can be formulated as wireless version of the NP-hard Virtual Network Embedding (VNE) problem, for which various heuristics exist. We propose a Reinforcement Learning (RL) framework, which relies on Q-Learning and uses either Greedy Epsilon or Epsilon Decay for exploration. We compare both exploration methods to the result of an optimization approach and show empirically that the RL framework achieves good results in terms of network delay within few number of steps.

Overview of Touché 2020: Argument Retrieval - Bondarenko, Alexander; Fröbe, Maik; Beloucif, Meriem; Gienapp, Lukas; Ajjour, Yamen; Panchenko, Alexander; Biemann, Chris; Stein, Benno; Wachsmuth, Henning; Potthast, Martin; Hagen, Matthias (CEUR Workshop Proceedings)

Spannungszustandsabhängige Schädigungsmodellierung zum Halbhohlstanznieten - Otroshi, Mortaza; Meschut, Gerson (Umformtechnik Blech Rohre Profile)

Brief Announcement: Gathering in Linear Time: A Closed Chain of Disoriented & Luminous Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Stabilization, Safety, and Security of Distributed Systems - 22nd International Symposium, SSS 2020, Austin, Texas, USA, November 18-21, 2020, Proceedings)

Hybrid coupled mode modelling of the evanescent excitation of a dielectric tube by semi-guided waves at oblique angles - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Optical and Quantum Electronics)
A dielectric step-index optical fiber with tube-like profile is considered, being positioned with a small gap on top of a dielectric slab waveguide. We propose a 2.5-D hybrid analytical/numerical coupled mode model for the evanescent excitation of the tube through semi-guided waves propagating in the slab at oblique angles. The model combines the directional polarized modes supported by the slab with analytic solutions for the TE-, TM-, and orbital-angular-momentum (OAM) modes of the tube-shaped fiber. Implementational details of the scheme are discussed, complemented by finite-element simulations for verification purposes. Our results include configurations with resonant in-fiber excitation of OAM modes with large orbital angular momentum and strong field enhancement.
Keywords: tet_topic_waveguides

Platform-independent Reputation and Qualification System for Crowdwork - Hemsen, Paul; Hesse, Marc; Löken, Nils; Nouri, Zahra (2nd Crowdworking Symposium)

Monocular Depth Estimation via Listwise Ranking using the Plackett-Luce model - Lienen, Julian; Hüllermeier, Eyke (arXiv:2010.13118)
In many real-world applications, the relative depth of objects in an image is crucial for scene understanding, e.g., to calculate occlusions in augmented reality scenes. Predicting depth in monocular images has recently been tackled using machine learning methods, mainly by treating the problem as a regression task. Yet, being interested in an order relation in the first place, ranking methods suggest themselves as a natural alternative to regression, and indeed, ranking approaches leveraging pairwise comparisons as training information ("object A is closer to the camera than B") have shown promising performance on this problem. In this paper, we elaborate on the use of so-called listwise ranking as a generalization of the pairwise approach. Listwise ranking goes beyond pairwise comparisons between objects and considers rankings of arbitrary length as training information. Our approach is based on the Plackett-Luce model, a probability distribution on rankings, which we combine with a state-of-the-art neural network architecture and a sampling strategy to reduce training complexity. An empirical evaluation on benchmark data in a "zero-shot" setting demonstrates the effectiveness of our proposal compared to existing ranking and regression methods.

Plurality Consensus in Hybrid Networks - Yeole, Paresh Kishor

Nonlinear dielectric properties of random paraelectric-dielectric composites - Myroshnychenko, Viktor; Smirnov, Stanislav; Jose, Pious Mathews Mulavarickal; Brosseau, Christian; Förstner, Jens (Acta Materialia)
The challenge of designing new tunable nonlinear dielectric materials with tailored properties has attracted an increasing amount of interest recently. Herein, we study the effective nonlinear dielectric response of a stochastic paraelectric-dielectric composite consisting of equilibrium distributions of circular and partially penetrable disks (or parallel, infinitely long, identical, partially penetrable, circular cylinders) of a dielectric phase randomly dispersed in a continuous matrix of a paraelectric phase. The random microstructures were generated using the Metropolis Monte Carlo algorithm. The evaluation of the effective permittivity and tunability were carried out by employing either a Landau thermodynamic model or its Johnson’s approximation to describe the field-dependent permittivity of the paraelectric phase and solving continuum-electrostatics equations using finite element calculations. We reveal that the percolation threshold in this composite governs the critical behavior of the effective permittivity and tunability. For microstructures below the percolation threshold, our simulations demonstrate a strong nonlinear behaviour of the field-dependent effective permittivity and very high tunability that increases as a function of dielectric phase concentration. Above the percolation threshold, the effective permittivity shows the tendency to linearization and the tunability dramatically drops down. The highly reduced permittivity and extraordinarily high tunability are obtained for the composites with dielectric impenetrable disks at high concentrations, in which the triggering of the percolation transition is avoided. The reported results cast light on distinct nonlinear behaviour of 2D and 3D stochastic composites and can guide the design of novel composites with the controlled morphology and tailored permittivity and tunability.

Increased load bearing capacity of mechanically joined FRP/metal joints using a pin structured auxiliary joining element - Heyser, Per; Sartisson, Vadim; Meschut, Gerson; Droß, Marcel; Dröder, Klaus (Materials Testing)

Essays on Cooperation in Differential Games - Hoof, Simon

Avoidance of liquid metal embrittlement during resistance spot welding by heat input dependent hold time adaption - Böhne, Christoph; Meschut, Gerson; Biegler, Max; Rethmeier, Michael (Science and Technology of Welding and Joining)

Resistance spot welding simulation can determine the critical stress- and strain-conditions leading to liquid metal embrittlement formation - Biegler, Max; Rethmeier, Michael; Böhne, Christoph; Meschut, Gerson (Joining in Car Body Engineering)

Defining and Verifying Durable Opacity: Correctness for Persistent Software Transactional Memory - Bila, Eleni; Doherty, Simon; Dongol, Brijesh; Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (Formal Techniques for Distributed Objects, Components, and Systems - 40th IFIP WG 6.1 International Conference, FORTE 2020, Held as Part of the 15th International Federated Conference on Distributed Computing Techniques, DisCoTec 2020, Valletta, Malta, June 15-19, 2020, Proceedings)

Consistency Analysis of AUTOSAR Timing Requirements - Beringer, Steffen; Wehrheim, Heike (Proceedings of the 15th International Conference on Software Technologies, ICSOFT 2020, Lieusaint, Paris, France, July 7-9, 2020)

Verification Artifacts in Cooperative Verification: Survey and Unifying Component Framework - Beyer, Dirk; Wehrheim, Heike (Leveraging Applications of Formal Methods, Verification and Validation: Verification Principles - 9th International Symposium on Leveraging Applications of Formal Methods, ISoLA 2020, Rhodes, Greece, October 20-30, 2020, Proceedings, Part I)

Fundamental Approaches to Software Engineering - 23rd International Conference, FASE 2020, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2020, Dublin, Ireland, April 25-30, 2020, Proceedings

Tests and Proofs - 14th International Conference, TAP@STAF 2020, Bergen, Norway, June 22-23, 2020, Proceedings [postponed]

Testing Monotonicity of Machine Learning Models - Sharma, Arnab; Wehrheim, Heike (CoRR)

Mapping postprandial responses sets the scene for targeted dietary advice - Brand-Miller, Jennie; Buyken, Anette (Nature Medicine)

The relationship between differences in students’ computer and information literacy and response times: an analysis of IEA-ICILS data - Heldt, Melanie; Massek, Corinna; Drossel, Kerstin; Eickelmann, Birgit (Large-scale Assessments in Education)
Abstract Background Due to the increasing use of information and communication technology, computer-related skills are important for all students in order to participate in the digital age (Fraillon, J., Ainley, J., Schulz, W., Friedman, T. & Duckworth, D. (2019). Preparing for life in a digital world: IEA International Computer and Information Literacy Study 2018 International Report. Amsterdam: International Association for the Evaluation of Educational Achievement (IEA). Retrieved from https://www.iea.nl/sites/default/files/2019-11/ICILS%202019%20Digital%20final%2004112019.pdf ). Educational systems play a key role in the mediation of these skills (Eickelmann. Second Handbook of Information Technology in Primary and Secondary Education. Cham: Springer, 2018). However, previous studies have shown differences in students’ computer and information literacy (CIL). Although various approaches have been used to explain these differences, process data, such as response times, have never been taken into consideration. Based on data from the IEA-study ICILS 2013 of the Czech Republic, Denmark and Germany, this secondary analysis examines to what extent response times can be used as an explanatory approach for differences in CIL also within different groups of students according to student background characteristics (gender, socioeconomic background and immigrant background). Methods First, two processing profiles using a latent profile analysis (Oberski, D. (2016). Mixture Models: Latent Profile and Latent Class Analysis. In J. Robertson & M. Kaptein (Eds.), Modern Statistical Methods for HCI (pp. 275–287). Switzerland: Springer. 10.1007/978-3-319-26633-6 ) based on response times are determined—a fast and a slow processing profile. To detect how these profiles are related to students’ CIL, also in conjunction with students’ background characteristics (socioeconomic and immigrant background), descriptive statistics are used. Results The results show that in the Czech Republic and Germany, students belonging to the fast processing profile have on average significantly higher CIL than students allocated to the slow processing profile. In Denmark, there are no significant differences. Concerning the student background characteristics in the Czech Republic, there are significant negative time-on-task effects for all groups except for students with an immigrant background and students with a high parental occupational status. There are no significant differences in Denmark. For Germany, a significant negative time-on-task effect can be found among girls. However, the other examined indicators for Germany are ambiguous. Conclusions The results show that process data can be used to explain differences in students’ CIL: In the Czech Republic and Germany, there is a correlation between response times and CIL (significant negative time-on-task effect). Further analysis should also consider other aspects of CIL (e.g. reading literacy). What becomes clear, however, is that when interpreting and explaining differences in competence, data should also be included that relates to the completion process during testing.

Goal Achievement, Subsequent User Effort and the Moderating Role of Goal Difficulty - Gutt, Dominik; von Rechenberg, Tobias; Kundisch, Dennis (Journal of Business Research)

Enhancing social cohesion in PE classes within an intercultural learning program: results of a quasi-experimental intervention study - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Physical Education and Sport Pedagogy)

"Solange dieser Mann gut Deutsch sprechen kann, ist auch kein Problem...": Evaluative Reaktionen auf einen L2-Akzent aus Sicht von Sprecher*innen - Müller, Mareike; Settinieri, Julia (Fremdsprachen Lehren und Lernen)
This article investigates learners’ accounts of and reactions to interlocutors’ evaluations of their L2 pronunciation. Previous studies demonstrate both the pervasiveness of social evaluation processes in native and non-native speaker interactions and the impact of learners’ beliefs about pronunciation on their learning and communicative behavior. Adding to these strands of research, this project sheds light on how learners perceive evaluative reactions to their accents by native speakers and the relationship between such evaluations and learners’ reported evaluative, emotional and behavioral responses. The study draws on 8 international students at a German university. The data were collected in semi-structured interviews and analyzed within the framework of qualitative content analysis. The results give insight into conditions and strategies that may support learners in establishing constructive interpretations of the effects of their accents on their social acceptance.

Systematik zur Digitalisierung von Produktprogrammen - Echterfeld, Julian

Systematik zur integrativen Entwicklung von mechatronischen Produkten und deren Prüfmittel - Lukei, Meinolf

Die Anbahnung einer forschenden Grundhaltung im Praxissemester – eine empirische Analyse von Bedingungen und Entwicklungsverläufen - Homt, Martina

Above 60 GHz Bandwidth 10 GS/s Sampling Rate Track-and-Hold Amplifier in 130 nm SiGe BiCMOS Technology - Wu, Liang; Weizel, Maxim; Scheytt, Christoph (2020 IEEE International Symposium on Circuits and Systems (ISCAS))
This paper presents a broadband track-and-hold amplifier (THA) based on switched-emitter-follower (SEF) topology. The THA exhibits both large- and small-signal bandwidth exeeding 60 GHz. It achieves an effective number of bits (ENOB) of 7 bit at 34 GHz input frequency and an ENOB of >5 bit over the whole input frequency bandwidth at sampling rate of 10 GS/s. Much higher sampling rates are possible but lead to somewhat worse performance. The chip was fabricated in a 130 nm SiGe BiCMOS technology from IHP (SG13G2). It draws 78 mA from a -4.8 V supply voltage, dissipating 375 mW.

Sensitivity Analysis of a Low-Power Wake-Up Receiver Using an RF Barker Code SAW Correlator and a Baseband Narrowband Correlator - Abughannam, Saed; Scheytt, Christoph (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC 2020))
In this paper we propose a novel low-power receiver architecture which uses a direct-detection receiver in combination with a 2.44 GHz 13 bit Barker Code SAW correlator for improvement of co-channel interference. Furthermore, to improve receiver sensitivity, a narrowband baseband correlator which uses pulse position modulation (PPM) is proposed. The receiver can be used as a Wake-up Receiver (WuRx) in Wireless Sensor Networks (WSN) to minimize the power dissipation and provide asynchronous and on-demand data communication. We present a rigorous analysis of the receiver. It shows that the RF front-end (SAW correlator and envelope detector) alone suffers from poor sensitivity due to the high baseband bandwidth and the absence of an RF low noise amplifier. However, by adding the narrowband correlator with an innovative Pulse Position Modulation (PPM) scheme, the overall sensitivity of the receiver reaches -63.1 dB with an improvement of 17.7 dB due to the use of the narrowband correlator that reduces the baseband bandwidth from 50 to 0.84 MHz. By scaling the narrowband correlator bandwidth further down, the receiver sensitivity can be further improved.

A Scalable Platform for QEMU Based Fault Effect Analysis for RISC-V Hardware Architectures - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2020 - Methods and Description Languages for Modelling and Verification of Circuits and Systems; GMM/ITG/GI-Workshop)
Fault effect simulation is a well-established technique for the qualification of robust embedded software and hardware as required by different safety standards. Our article introduces a Virtual Prototype based approach for the fault analysis and fast simulation of a set of automatically generated and target compiled software programs. The approach scales to different RISC-V ISA standard subset configurations and is based on an instruction and hardware register coverage for automatic fault injections of permanent and transient bitflips. The analysis of each software binary evaluates its opcode type and register access coverage including the addressed memory space. Based on this information dedicated sets of fault injected hardware models, i.e., mutants, are generated. The simulation of all mutants conducted with the different binaries finally identifies the cases with a normal termination though executed on a faulty hardware model. They are identified as a subject for further investigations and improvements by the implementation of additional hardware or software safety countermeasures. Our final evaluation results with automatic C code generation, compilation, analysis, and simulation show that QEMU provides an adequate efficient platform, which also scales to more complex scenarios.

Analysis, Design and Implementation of a Fully Integrated Analog Front-End for Microwave RFIDs at 5.8 GHz to be Used with Compact MIMO Readers - Haddadian, Sanaz; Scheytt, Christoph (IEEE Journal of Radio Frequency Identification)
In this paper we present the system and circuit level analysis and feasibility study of applying microwave Radio Frequency Identification (RFID) systems with multipleinput multiple-output (MIMO) reader technology for tracking machining tools in multipath fading conditions of production environments. In the proposed system the MIMO reader interrogates single-antenna tags, and a high RFID frequency of 5.8 GHz is chosen to reduce the size of the reader's antenna array. According to the requirements dictated by the performed system analysis at 5.8 GHz, a low power fully integrated analog frontend (AFE) is designed and fabricated in a standard 65-nm CMOS technology for low power passive transponders. Performance of the Differential Drive Rectifier (DDR) topology as the core of the energy harvesting unit is investigated in detail. A multi-stage DDR power scavenging unit is dimensioned to provide a 1.2 V rectified voltage for 20-30 kQ load range, with a high power conversion efficiency (PCE) for high frequency and low input power level signals. The rectified voltage is then converted to a 1 V regulated voltage for the AFE and the baseband processor with 30 to 50 μW of estimated power consumption. Transistors with standard threshold voltage (VT) have been used for implementation. Measurements of the fabricated multi-stage configuration of the circuit show a maximum PCE of 68.8% at -12.46 dBm, and an input quality factor (Q-factor) of approximately 10. Amplitude-shift keying (ASK) demodulator and backscattering modulator with 80% modulation index, operating according to EPC-C1G2 protocol are applied for data transfer. The AFE consumes less than 1 μW in the reading mode. The AFE tag chip is 0.55 × 0.58 mm 2 .

Design and Fabrication of Barker Coded Surface Acoustic Wave (SAW) Correlator at 2.45 GHz for Low-Power Wake-up Receivers - Ballandras, Sylvain; Abughannam, Saed; Courjon, Emilie; Scheytt, Christoph (GeMiC 2020 - German Microwave Conference)
Low-power receivers use direct-detection receiver architecture for its design simplicity and its low power dissipation. However, the direct-detection based receivers suffer from co-channel interference which significantly degrades the communication reliability. Co-channel interference robustness can be improved by using a BPSK Barker code modulated Surface Acoustic Wave (SAW) correlator as a prior stage to the RF direct detection circuit. This paper reports in details the design, fabrication and measurements of a 2.45 GHz SAW correlator with 13 bits length Barker code. The device is fabricated on Lithium Niobate LiNbO3 substrate and it is composed of an input non-coded Inter Digital Transducers (IDT), a Piezoelectric substrate and an output coded IDT. The device wavelength λ is set to 1.6 μm, considering a phase velocity of the wave equal to 3970 m.s-1. Several configurations of the device were designed and fabricated, particularly varying the aperture and the non-coded IDT length to find out the optimal device configuration. All devices were found to operate with Insertion Loss (IL) ranging from 12 to 15 dB at 2.45 GHz with a tip probing measurement setup, while a packaged sample has an IL of 12.45 dB at 2.44 GHz mounted on a PCB with external 50 Ω LC matching network. Additionally, time-domain measurement for the packaged device shows that the output has a correlation peak with a peak-to-side-lobe (PSL) ratio of 4:1 for a -0.5 dBm input BPSK Barker code signal.